Experimental deterministic correction of qubit loss - Davide Vodola (Nature, 2020)
The successful operation of quantum computers relies on protecting qubits from decoherence and noise which, if uncorrected, will lead to erroneous results. These errors accumulate during an algorithm and thus correcting them becomes a key requirement for large-scale and fault-tolerant quantum information processors. Besides computational errors, which can be addressed by quantum error correction, the carrier of the information can also be completely lost or the information can leak out of the computational space. It is expected that such loss errors will occur at rates that are comparable to computational errors. Here we experimentally implement a full cycle of qubit loss detection and correction on a minimal instance of a topological surface code in a trapped-ion quantum processor. The key technique for this correction is a quantum non-demolition measurement via an ancillary qubit, which acts as a minimally invasive probe to detect absent qubits while only imparting the minimal quantum-mechanically possible disturbance on the remaining qubits. Upon detecting qubit loss, a recovery procedure is triggered in real-time, which maps the logical information onto a new encoding on the remaining qubits. Although the current demonstration is performed in a trapped-ion quantum processor, the protocol is applicable to other quantum computing architectures and error correcting codes, including leading 2D and 3D topological codes. These methods provide a complete toolbox for the correction of qubit loss that complements techniques to mitigate computational errors, which together constitute the building blocks for complete and scalable quantum error correction.